The foreign direct investment in central Africa : determinants and economics effects - (:unkn) unknown (My University, 2008)
The aim of this thesis is to analyse the impact of Foreign Direct Investment in Centra) Africa. The author uses the gravity Model to show that Natural resources still remain the first determinant of Foreign Direct Investment (FDI) in Centra) Africa, far ahead of the market size and the population. The structural equation model is also used to analyse the positive and negative effects of FDI on Economic growth in Central Africa. The result shows that the contribution of FDI in Cameroon was substantial, fair in Equatorial Guinea and Gabon and quite neal in Congo and Tchad.
Keywords: African Research